Does training matter? Exploring teachers' attitudes towards the inclusion of children with autism spectrum disorder in mainstream education in Ireland. Issue 7 (7th June 2022) - Leonard, Noelle M.; Smyth, Sinéad
ABSTRACT: Seventy-eight primary school teachers completed an online questionnaire comprised of demographic questions and a standardised measure of attitudes towards inclusion. It was found that the teachers who completed the questionnaire had predominantly negative or neutral attitudes towards the inclusion of children with Autism Spectrum Disorder (ASD) in mainstream education. Gender, number of years teaching experience, training in Special Educational Needs (SEN) and/or inclusion or type of training in SEN and inclusion did not influence attitudes. However, teachers who believed they had the adequate resources to facilitate inclusion had significantly more positive attitudes than teachers who did not believe they had the adequate resources to facilitate inclusion. Although future research is needed to further explore the impact of student profile on teacher attitudes towards the inclusion of students with ASD, thought needs to be given to the type and content of teacher training in SEN and inclusion.